Functional Analysis in the Institute of Mathematics of the National Academy of Sciences of Ukraine - Berezansky, Yu. M.; Gorbachuk, V. I.; Gorbachuk, M. L. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We give a brief survey of results on functional analysis obtained at the Institute of Mathematics of the Ukrainian National Academy of Sciences from the day of its foundation.